The Muhadatsah Program with Communicative and Contextual Approaches in Enhancing Students’ Speaking Skills (Kalam) at Ma'had Tahfidz Al-Qur'an Al-Amien Madura - Islam, Nur Izzatul; Ahmed, Bakri Mohammad Bkheet; Chamidah, Dewi; Bahri, Muhammad Riza Salsabila (Borneo Journal of Language and Education, 2025)
The Muhadatsah program is a key component of Arabic language instruction, delivered through dialogues that emphasize interactive, two-way communication between speakers and listeners. Communicative and contextual approaches are central to this method, aiming to develop students’ speaking skills (maharah kalam) for effective, real-life communication rather than focusing solely on grammar or vocabulary memorization. This study aims to: (1) describe the implementation of the Muhadatsah program using communicative and contextual approaches at Ma'had Tahfidz Al-Qur'an Al-Amien; (2) identify challenges and solutions in its implementation; and (3) analyze the program’s contribution to students' speaking proficiency. A qualitative descriptive approach was employed, focusing on the "Takmili" class of 40 female students at the Al-Amien Qur’an Memorization Institute in Brendowan, Sumenep, Madura. Data were collected through interviews, observations, and documentation, and analyzed using the Miles and Huberman model, which includes data reduction, display, and conclusion drawing. The program is conducted twice a week under the guidance of conversation instructors, using materials such as textbooks and audio recordings of native Arabic speakers. Lessons are designed to reflect students’ daily lives. Challenges include students' limited vocabulary and speaking confidence, and teachers' time constraints and varying student proficiency. Despite these challenges, the program significantly contributes to three areas: contextual vocabulary use, mastery of everyday expressions, and language enrichment across various topics and situations.